Antioxidant Activity, Sensory, Chemical, and Microbiology Characteristics of Muntok White Pepper (Piper Nigrum Linn.) Hard Candy - Rosy Hutami; Dwi Aryanti Nur’utami; Aulia Joana (Indonesian Journal of Applied Research (IJAR), 2021)
Muntok white pepper is the most recognized commodity of Indonesian in the world. One of the diversified products of white pepper is hard candy. This study aimed to determine the antioxidant activity, chemical, sensory, and microbiology characteristics of Muntok white pepper hard candy. The used experimental design was factorial completely randomized design, with the sucrose – glucose ratio as the first factor with two levels (50:50 and 70:30) and white pepper powder concentration as the second level with three levels (1%, 3%, and 5%). The product selection was based on the hedonic parameters. After getting the selected formulation, some tests were conducted, including antioxidant activity test by DPPH method, proximat analysis, TPC test, sensory evaluation, and energy content calculation. Selected Muntok white pepper hard candy formulation used a 50:50 sucrose – glucose ratio with 1% white pepper addition. It has a moisture content of 3.46%, ash content of 0.89%, fat of 12%, the protein content of 1.95%, reducing sugar of 11.31%, saccharose of 62.93%, TPC of 8x101 colonies/g, low antioxidant activity (IC 50) of 141208.03 mg/L, AEAC of 20.58 mg/100g vitamin C, the percent inhibition of 17.66%, the energy content of 365.44 kcal/100gr. The hedonic test result leads to be like by the panellists (5.57 -7.10 in 10 scales). Its sensory quality test results were leading to golden yellow (8.31), leading to spicy (5.58), no pepper smell (2.86), and leading to the hard texture (4.34). The selected product has confirmed the Indonesian National Standard of hard candy.